1987
DOI: 10.1071/pp9870341
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogenous Compatible Solutes in Native South Australian Plants

Abstract: Australian native flora was examined with nuclear magnetic resonance (n.m.r.) techniques for its content of nitrogenous compatible solutes. Plants were sampled from four habitats: two arid, one subhumid, and one saline estuarine marsh. Eight and two of the 15 plants in the subhumid area accumulated proline and glycinebetaine, respectively, whereas many of the plants in the two arid habitats accumulated these solutes. With only two exceptions plants in the saline marsh could be described as either proline accum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
1

Year Published

1994
1994
2011
2011

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 0 publications
0
7
1
Order By: Relevance
“…Seasonal effects may be difficult to detect when other sources of variation cannot be controlled during field studies. Other authors reported no relationship between organic solute concentration and osmotic stress during field studies (Naidu et al 1987, 2000, Poljakoff‐Mayber et al 1987), whereas in glasshouse studies organic solute concentrations in several species have responded to increasing salinity (Bar‐Nun and Poljakoff‐Mayber 1977, Banuls and Primo‐Millo 1992, Colmer et al 1996, Khan et al 1999, Naidu et al 1987), including the species investigated in this study (Carter et al 2006). However, although methyl proline and proline were not accumulated further above the relatively high levels already present during winter in foliage of M. cuticularis or C. obesa , concentrations were similar to those observed in saplings treated with 400 m M NaCl during a glasshouse study and greater than in unstressed controls (Carter et al 2006).…”
Section: Discussioncontrasting
confidence: 59%
“…Seasonal effects may be difficult to detect when other sources of variation cannot be controlled during field studies. Other authors reported no relationship between organic solute concentration and osmotic stress during field studies (Naidu et al 1987, 2000, Poljakoff‐Mayber et al 1987), whereas in glasshouse studies organic solute concentrations in several species have responded to increasing salinity (Bar‐Nun and Poljakoff‐Mayber 1977, Banuls and Primo‐Millo 1992, Colmer et al 1996, Khan et al 1999, Naidu et al 1987), including the species investigated in this study (Carter et al 2006). However, although methyl proline and proline were not accumulated further above the relatively high levels already present during winter in foliage of M. cuticularis or C. obesa , concentrations were similar to those observed in saplings treated with 400 m M NaCl during a glasshouse study and greater than in unstressed controls (Carter et al 2006).…”
Section: Discussioncontrasting
confidence: 59%
“…Sugars, polyols, amino acids, and quaternary ammonium compounds, e.g. betaines, have been most associated with osmotic adjustment in higher plant cells in response to osmotic stress (Flowers et al 1977Greenway and Munns 1980;Aspinall and Paleg 1981;Poljakoff-Mayber et al 1987;Rhodes 1987). The attributes of these molecules as "compatible" solutes include high solubility in water, relative metabolic inertness and minimal effects on charge balance (Yancey et al 1982;Somero 1986;Csonka 1989).…”
Section: Organic Osmotic Solute Accumulation In the Cytosolmentioning
confidence: 98%
“…In 23 Chenopodiaceae species collected from the field, or grown in controlled conditions, proline concentrations were <7.5% of those of glycinebetaine (Cavalieri and Huang 1979;Storey and Wyn Jones 1979;Gorham et al 1980;Briens and Larher 1982;Poljakoff-Mayber et al 1987;Pujol et al 2001). Glycinebetaine concentrations on a tissue water basis in expanding shoot tissues of the three Tecticornia species grown at 10-800 mM NaCl were 46-140 mM (0.37-0.90 mmol g −1 dry mass).…”
Section: Salt Tolerancementioning
confidence: 99%